The Influence of Price and Promotion on Consumer Preferences for Eco-Friendly Products at PT Karya Rappo Indonesia in Makassar City - Taufiqurrahman; Aulia; Sherry Adelia Natsir Kalla (Dinasti International Journal of Management Science, 2025)
This study aims to analyze the effect of price and promotion on consumer preferences for environmentally friendly products at PT Karya Rappo Indonesia in Makassar City. The research population is consumers who have purchased environmentally friendly products from PT Karya Rappo Indonesia in Makassar City. The population size cannot be determined with certainty due to the continuous increase in consumers. Determination of the sample size using the Malkhotra formula with the approach of the number of variables multiplied by 5, so that 120 respondents were obtained. The study used a quantitative approach with data collection through questionnaires. The results showed that the price (X1) and promotion (X2) variables had a positive and significant effect <0.05 on consumer preferences (Y) for environmentally friendly products. The promotion variable has a more dominant influence with a regression coefficient of 0.489 than the price variable with a regression coefficient of 0.425.